2021
DOI: 10.2147/rmhp.s305959
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, Practices, and Related Factors Towards COVID-19 Prevention Among Patients at University Medical Center Ho Chi Minh City, Vietnam

Abstract: This study measured the level of knowledge, attitudes and practices towards COVID-19 prevention and examined associated factors among patients at a national tertiary general hospital in Vietnam. Methods: Adult patients admitted to University Medical Center during research period were recruited in a cross-sectional study, which employed a convenience sampling method with a 4-component questionnaire in order to examine the patients' consciousness towards COVID-19 spreading prevention based on four aspects: demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
2
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 21 publications
7
22
2
13
Order By: Relevance
“…Compared to the majority of the studies in the literature, our study found low good practice regarding COVID-19 preventive measures. The practice of COVID-19 preventive measures in the Jimma community was lower compared to the findings from Iran ( 17 ), Nigeria ( 18 ), Lebanon ( 19 ), Venezuela ( 20 ), and Vietnam ( 21 ).…”
Section: Discussioncontrasting
confidence: 57%
“…Compared to the majority of the studies in the literature, our study found low good practice regarding COVID-19 preventive measures. The practice of COVID-19 preventive measures in the Jimma community was lower compared to the findings from Iran ( 17 ), Nigeria ( 18 ), Lebanon ( 19 ), Venezuela ( 20 ), and Vietnam ( 21 ).…”
Section: Discussioncontrasting
confidence: 57%
“…Peruvians with symptoms of COVID-19 with a secondary and superior educational level were less likely not to use health services than those without a formal education. In this regard, it has been reported that having a higher educational level is significantly associated with greater knowledge, positive attitudes, and good practices regarding the prevention of the spread of COVID-19 [ 32 ]. The above could explain what happened in the Peruvian population.…”
Section: Discussionmentioning
confidence: 99%
“…Kiến thức phòng chống COVID-19: Triệu chứng (thường gặp, ít gặp, nghiêm trọng), đường lây, phòng ngừa (Tiêm vắc xin, giữ khoảng cách, mang khẩu trang, rửa tay, che miệng và mũi khi kho hoặc hắc hơi, tự cách ly và khai báo y tế khi nghi ngờ mắc COVID-19). Sử dụng thang đo Likert 5 mức độ từ rất không đồng ý, không đồng ý, không biết, đồng ý đến rất đồng ý, tổng điểm kiến thức là 60 điểm (≥80%: Tốt; 60-79%: Trung bình; <60%: Kém) [3], [4], [6].…”
Section: Phương Pháp Nghiên Cứuunclassified
“…Thái độ phòng chống COVID-19: Tiêm vắc xin, mang khẩu trang, rửa tay, giữ khoảng cách, không tụ tập, khai báo y tế. Sử dụng thang đo Likert 5 mức độ từ rất không đồng ý, không đồng ý, trung lập, đồng ý đến rất đồng ý, tổng điểm thái độ là 30 điểm (≥80%: Tích cực; 60-79%: Trung lập; <60%: Tiêu cực) [3], [4], [6].…”
Section: Phương Pháp Nghiên Cứuunclassified
See 1 more Smart Citation